Size Matters in Legal Ethics: Contrasting Mediating Mechanisms of Reputational Capital - Raja Frans; Erico Hamdani; Dadan Abdul Aziz Mubarok; Nunung Ayu Sofiati (International Journal of Management, Economic and Accounting, 2026)
The efficacy of digital signaling in credence goods markets remains paradoxical: while visibility tools are universal, their reputational impact is highly context-dependent. This study challenges the prevailing "one-size-fits-all" assumption in legal services marketing by examining firm size as a critical boundary condition. Drawing on a synthesis of Signaling Theory and Institutional Theory, we posit that the mechanism of building reputational capital differs fundamentally between market challengers (small firms) and incumbents (large firms). Data were collected from 126 strategic elites (partners/founders) in the Indonesian legal sector, representing a high-uncertainty emerging market context. The model was tested using Partial Least Squares Multi-Group Analysis (PLS-MGA). The results confirm a sharp strategic dichotomy. For small firms, professional ethics functions as an "offensive weapon," where digital signaling intensity yields a massive impact on ethical legitimacy , effectively overcoming the liability of newness. Conversely, for large firms, ethics serves merely as a "defensive shield" or hygiene factor, with a significantly lower conversion rate , as their reputation is already "embedded" in historical institutional structures. Theoretically, this research introduces the concept of "Signal Elasticity," demonstrating that the reputational yield of ethical signaling is structurally contingent. These findings provide tailored strategic prescriptions for "Davids" and "Goliaths" in the digital legal marketplace, suggesting that while challengers must prioritize high-fidelity signaling, incumbents should focus on maintaining institutional buffers.